The Self-Defeating Liberal International Order: Organized Hypocrisy and Legitimacy Deficit - Mirah Satria Alamsyah; Miftah Farid Darussalam (JUSS (Jurnal Sosial Soedirman), 2026)
This study argues that the Liberal International Order (LIO) is self-defeating, with its deterioration driven more by endogenous than exogenous factors. The principal endogenous factor identified is the LIO's organized hypocrisy, a condition in which the order's foundational norms, particularly self-determination and non-interference, are simultaneously upheld in discourse and systematically violated in practice by its own principal proponents. Drawing on the organized hypocrisy framework developed by Stephen C. Krasner, this study analyzes norm violations across four modalities: convention, contract, coercion, and imposition. It further argues that this organized hypocrisy contributes to a legitimacy deficit within the LIO, as evidenced by declining trust in the United Nations, an increasingly unfavorable global perception of the United States as the order's principal proponent, and the behavior of LIO beneficiaries who are actively seeking institutional alternatives such as BRICS. Employing a qualitative desk-based research method, this study concludes that the LIO is structurally self-defeating: its expansive liberal ambitions generate actions that undermine the sovereign norms upon which its own legitimacy rests.